Belowground persistence types relevant to severe disturbance - Klimešová, Jitka; Laughlin, Daniel C; Siebert, Frances; Bergmann, Joana; Tumber-Dávila, Shersingh Joseph; Andraczek, Karl; Bombo, Aline B [UNESP]; Bruelheide, Helge; Fan, Ying; Freschet, Grégoire T; Hennecke, Justus; Howard, Cody Coyotee; et al. (Elsevier, 2025)
Despite recent advances in plant trait ecology, we identified a knowledge gap in understanding how plants strategize to cope with severe and recurrent disturbances. Here, we propose a new classification system based on three hierarchical binary attributes: woodiness, reflecting longevity of plant structures; clonality, indicating the ability to regenerate from both above- and belowground organs; and resprouting ability, referring to the ability to replace aboveground organs. This framework results in six Belowground Persistence Types (BPTs): 1, herbaceous seeder; 2, herbaceous non-clonal resprouter; 3, herbaceous clonal resprouter; 4, woody seeder; 5, woody non-clonal resprouter; and 6, woody clonal resprouter. This proposed classification system opens new avenues for research, especially concerning plant distributions in a world experiencing increasingly frequent and severe disturbance events.